INTEGRATION OF MILITARY TRAINING INTO HIGHER EDUCATION PROGRAMS - Tatyana Yu. Tsibizova (Moscow Polytechnic University, 2016)
This article is about the problematic research regarding integration of military preparation into the basic professional higher education programs. The author puts the main emphasis on reproduction of soldiers', sailors', sergeants' and reserve officers' personnel potential in higher education institutions. The major goal of such preparation is to ensure accumulation of highly qualified military-trained staff reserve. The concept of military training integration into bachelor and specialist courses is considered in several aspects: military training contents, military training arrangement, military training implementation, results' receipt. It is shown, that the system of military training integration into higher education programs is effective, incentive and allowing to prepare quality specialists for Military Forces of the Russian Federation.